Bartter Syndrome, a Rare Cause of Malnutrition in Children: Case Report - Khaliq, Abdul; ., Rifayatullah; Ambreen, Aneela (Journal of Gandhara Medical and Dental Science, 2016)
Three and half year old Haleema presented to OPD with complaints of failure to thrive polydipsia and polyuria. In past she visited different clinicians and hospitals. Scrutiny of the previous record showed alkalosis persistently, but other electrolytes values were different from different labs. We admitted her and investigations were repeated, which showed hypo-kalemia, hypo-chloremia, hypo-natremia, metabolic alkalosis, hyper-calciuria, and normal urine osmolality and specific gravity. Her plasma rennin and aldosterone level were also raised. She was discharged on treatment for Bartter syndrome. On follow up, 15 days later her weight and clinical symptoms were improved.